TOURISM POLICY MAKING DURING AN EMERGENCY: The Case of Yogyakarta City during COVID-19 Pandemic - Sarah Meirina Sari; Janianton Damanik (Magister Ilmu Administrasi Publik, 2021)
This study describes the public policy making process in Yogyakarta during the COVID-19 pandemic by determining the level of consistency of the government policy in opening and closing tourist attractions and its relationship to the decision of the possession of a COVID-19 free letter. The qualitative method was used because the approach was deemed capable of identifying various perspectives and points of view of the reality related to the process of tourism policy making during the COVID-19 pandemic condition in Yogyakarta City. The results showed that policies made were plagued by lack of adequate preparation and consistency. Not all tourist destinations were closed during the pandemic to prevent the spread of COVID-19. The decision did not have strong legality because as it was based on executive orders. Consequently, weak policy framework had adverse impact on cases of COVID-19. The surge in COVID-19 cases was also as a result of disagreement among the executives on the kind of sanctions that were meted out to violators of health protocols and the ineffectiveness of sanctions given. The implementation of the COVID-19 free letter for tourists from certain zones did not guarantee that visitors were free from COVID19. Policy recommendations for inconsistent and unequivocal policy implementation are expected to be further formulated. Thus, the policy implementers could adopt a flexible approach in interpreting policies in a proper manner.